2019
DOI: 10.3390/w11040725
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Improving Integration in National End-to-End Flood Forecasting Systems: An Overview of the FFIR (Flooding From Intense Rainfall) Programme

Abstract: Recent surface-water and flash floods have caused millions of pounds worth of damage in the UK. These events form rapidly and are difficult to predict due to their short-lived and localised nature. The interdisciplinary Flooding From Intense Rainfall (FFIR) programme investigated the feasibility of enhancing the integration of an end-to-end forecasting system for flash and surface-water floods to help increase the lead time for warnings for these events. Here we propose developments to the integration of an op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 59 publications
(67 reference statements)
1
43
0
Order By: Relevance
“…Before developing a surface water forecasting system, it is important to establish realistic aims for the system that balance the end‐user requirements and the scientific and practicality feasibility (Flack, Skinner, et al, 2019). There are two recent developments that have been fundamental to making these discussions possible.…”
Section: The Challenge Of Surface Water Flood Forecastingmentioning
confidence: 99%
See 2 more Smart Citations
“…Before developing a surface water forecasting system, it is important to establish realistic aims for the system that balance the end‐user requirements and the scientific and practicality feasibility (Flack, Skinner, et al, 2019). There are two recent developments that have been fundamental to making these discussions possible.…”
Section: The Challenge Of Surface Water Flood Forecastingmentioning
confidence: 99%
“…Moore et al (2015) concluded that due to run time constraints, there were limited linked hydrological and hydrodynamic models that had the potential to run in real time and those that could potentially be used in this way had not been developed with continuous updating of the system states in mind (Moore, Bell, Cole, & Jones, 2007; Speight et al, 2018). As computational power has increased over the past few years and cloud computing and graphical processing units (GPUs) have developed rapidly, these new technologies have emerged as a realistic and affordable way to run computationally demanding surface water flooding models in less time (see Flack, Skinner, et al, 2019; Glenis, Kutija, & Kilsby, 2018; Xia, Liang, Ming, & Hou, 2017). The benefit of real‐time hydrodynamic simulations is the ability to directly model the forecast spatial variability of rainfall on inundation and impacts at a city scale.…”
Section: Approaches To Surface Water Flood Forecastingmentioning
confidence: 99%
See 1 more Smart Citation
“…The FFIR programme described itself as "A five year NERC funded programme aiming to reduce the risk of damage and loss of life caused by surface water and flash floods" (Flooding from Intense Rainfall, 2019). The programme, based in and focussed on the UK, brought to-gether experts from several universities, environmental consultancies, the Met Office, the Environment Agency, and the British Geological Survey to better understand the role intense and localised rainfall events had on both rural and urban flooding, with a strong focus on the end-to-end forecasting on events (Dance et al, 2019;Flack et al, 2019). Thunderstorms, driven by strong convection in summer months, form and dissipate rapidly and can be highly localised covering just a 1-3 km wide area.…”
Section: The Research Contextmentioning
confidence: 99%
“…Therefore, there is an urge for measures to protect people and property from natural disasters [4][5][6]. Suppose the area and size of the damage can be predicted before the actual disaster then it can help to prevent and make adequate preparation for disaster management [7][8][9]. Therefore, studies were conducted to predict the damage.…”
Section: Introductionmentioning
confidence: 99%